Performance characteristics of divergent chimney solar updraft tower plant. (6th March 2020) - Das, Pritam; V.P., Chandramohan
Summary: A 3D computational model was developed to investigate the influence of divergence angle of chimney ( θ ch ) on the flow and performance characteristics of solar updraft tower (SUT) plant. The diameters of the chimney ( D ch )i and air entrance gap ( e ) selected for numerical simulations were 0.6 m and 0.1 m, respectively. Parametric study was carried out by varying θ ch from 1° to 5° for different solar fluxes (600‐1200 Wm −2 ) and the outcomes were compared with cylindrical chimney ( θ ch = 0°) SUT (CC‐SUT) plant. The effect of ambient temperature on the performance was also studied. A turbulent model (renormalization group k‐ɛ ) was incorporated for considering the turbulence effect. Discrete ordinates model was used for estimation of radiation heat transfer inside the setup. It was found that the velocity of air at the chimney base was enhanced by 59.4% compared to a CC‐SUT plant. From the parametric study, it was observed that θ ch = 2° gives superior performance to the system than any other angle. Also, maximum performance was achieved at higher solar flux ( I ). The average absorber plate temperature increased from 313.3 to 350.3 K with increase in solar flux from 600 to 1200 Wm −2 . The overall efficiency, and theoretical and actual power outputs of the divergent chimney‐SUT system were estimated and they were 0.0278%, 4.01 and 2.68 W, respectively. The net exergy efficiency ( ψ net ) of the system increased from 0.98% to 19.41% with increase in I from 600 to 1200 Wm −2 at θ ch = 2°. There was 55.2% increase in ψ net when θ ch increased from 1° to 2° and at I = 1200 Wm −2 . Correlations were developed for the prediction of ψ net for different θ ch and at different I . Abstract : A 3D numerical model developed for divergent‐type solar updraft tower (SUT) plant. The effect of chimney divergent angle ( θ ch ) is investigated on flow and performance parameters. Exergy analysis of divergent type SUT is performed.